Integrating strength and conditioning training and golf practice during the golf season: Approaches and perceptions of highly skilled golfers - Bliss, A.; Langdown, B. (International Journal of Sports Science & Coaching, 2023)
Contemporary evidence has demonstrated strength and conditioning (S&C) training benefits golf performance, primarily by improving clubhead speed. However, no empirical data exist that describe how, or even if, golfers integrate their S&C training and golf practice. Therefore, the aim of this study was to investigate the perceptions and practices of skilled golfers with regards to planning the season and how S&C is structured in the golf year. Sixty-five (male n = 48; female n = 17) Category 1 amateur (n = 50) and professional (n = 15) golfers completed a mixed-methods online survey. Survey answers were either golf practice or S&C training focused. Results showed the majority of golfers engage with S&C training (n = 44; 67.7%) and follow a programme (n = 53. 81.5%). Contrastingly, they reported having little structure for golf practice, choosing to have no annual plan (n = 14; 21.9%), have a reactive approach (n = 22. 34.9%) based on recent performances or training what feels appropriate/enjoyable (n = 15; 23.8%). Golfers reported they adjust their training around competition (n = 47; 74.6%) but with various approaches. The dichotomous and contradictory responses received across multiple answers demonstrate that continued education and research are required to help golfers integrate S&C training with their golf practice.